Strategy for Selecting Sustainable Tourism Indicators for the Gaspésie and Îles de la Madeleine Regions - Rajaonson, Juste; Tanguay, Georges (Téoros, 2012)
This article describes the creation of a grid of sustainable tourism indicators, specifically the strategy adopted by the Gaspésie and Îles de la Madeleine regions of Québec. First, a list of indicators recognized by experts, which systematically cover the dimensions of sustainable tourism, was compiled. In the second step, the indicators were coordinated with the sustainable tourism policy framework of each region, to operationalize the indicators while preserving their validity. This two-step strategy led to identification of a list of recognized and measurable sustainable tourism indicators consistent with the tourism policy of each region. This approach thus minimizes the risks of instrumentalization of the concept of sustainable tourism, and guarantees the validity of the assessment and follow-up approaches in this area.